Fatigue improvement and residual stress relaxation of shot-peened alloy steel DIN 34CrNiMo6 under axial loading - Leguinagoicoa, Nelson; Albizuri, Joseba; Larrañaga, Aitor (International journal of fatigue, 2022)
•Shot-peening process, compared with machined specimens, increases by 21.8% fatigue limit.•Quasi-static tests show more stress relaxation with compressive loads.•High stress magnitudes produce relaxation along the complete fatigue life.•Surface stresses relaxation model for SP is obtained.•FWHM is a good indicator for defining the relaxation process. Shot-peening treatment was applied to a quenched and tempered DIN 34CrNiMo6 steel to improve its high-cycle R: −1 axial fatigue strength. Compared with the machined condition, the increase in the fatigue limit was 21.8%. S-N curves for shot-peened and the as machined condition were presented and compared with those obtained in previous research for rotating bending fatigue, including curves for mirror-polished specimens. The applied shot-peening treatment in this work (Isp: 8A and 200% coverage) for quenched and tempered (Q + T) DIN 34CrNiMo6 steel introduced a compressive residual stress field and an increase in surface roughness, as well as minor variations in microstructure, hardness and the FWHM (full width of the diffraction peak at half maximum intensity) parameter. The introduced compressive residual stress field tended to reduce when an external stress is applied. This was due to the onset of plastic strain. In this paper, two types of quasi-static tests were conducted by applying an axial stress with six different magnitudes and in the two directions (compressive or tensile). This was in order to assess their influence on the relaxation of surface residual stresses. Due to the introduced compressive residual stresses, if the applied stress was compressive, the onset of plastic deformations was achieved with a lower stress magnitude. In addition, surface residual stress relaxation under cyclic applied stress was evaluated at four different stress magnitudes. Due to the cyclic-softening behaviour of this Q + T steel, its cyclic mechanical properties must be considered to assess the onset of plastic strains. With the experimental data, a logarithmic model to predict the evolution of surface residual stresses with the number of cycles for different applied stress magnitudes was presented.